The Effect of Artificial Intelligence on Digital Marketing Management of MSMEs - Suhroji Adha; Irawan Irawan; Enji Azizi; Hero Wirasmara Kusuma; Mira Nurhikmat (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The advancement toward the Society 5.0 era has encouraged MSMEs to increasingly adopt artificial intelligence in various business activities, particularly in digital marketing practices. However, empirical evidence examining the role of artificial intelligence in supporting digital marketing management among MSMEs, especially in developing countries, remains limited. This study investigates the influence of artificial intelligence utilization on digital marketing management among MSMEs in the Society 5.0 era. A quantitative approach was employed through a survey involving MSMEs that actively utilize digital technologies in their marketing activities. The collected data were analyzed using linear regression analysis with the assistance of SPSS software. The findings reveal that artificial intelligence utilization has a positive and statistically significant effect on digital marketing management among MSMEs. These results indicate that the integration of artificial intelligence into digital marketing activities contributes to improving marketing effectiveness and strengthening MSMEs’ competitiveness in the Society 5.0 era. Furthermore, this study contributes to the literature on technology-based digital marketing and provides practical implications for MSME practitioners and policymakers.